iNOS contributes to heart failure with preserved ejection fraction through mitochondrial dysfunction and Akt S-nitrosylation - Guo, Yongzheng; Wen, Junjie; He, An; Qu, Can; Peng, Yuce; Luo, Suxin; Wang, Xiaowen (Journal of advanced research, 2023)
[Display omitted] •Combination of HDF and L-NAME induced cardiac mitochondrial dysfunction and HFpEF phenotype.•Both long-term and short-term iNOS inhibition mitigated mitochondrial dysfunction and oxidative stress in HFpEF heart.•Akt S-nitrosylation was involved into the development of HFpEF.•Both long-term and short-term iNOS inhibition reduced Akt S-nitrosylation and rescued HFpEF phenotype. Despite the high morbidity and mortality of heart failure with preserved fraction (HFpEF), there are currently no effective therapies for this condition. Moreover, the pathophysiological basis of HFpEF remains poorly understood. The aim of the present study was to investigate the role of inducible nitric oxide synthase (iNOS) and its underlying mechanism in a high-fat diet and Nω-nitro-L-arginine methyl ester-induced HFpEF mouse model. The selective iNOS inhibitor L-NIL was used to examine the effects of short-term iNOS inhibition, whereas the long-term effects of iNOS deficiency were evaluated using iNOS-null mice. Cardiac and mitochondrial function, oxidative stress and Akt S-nitrosylation were then measured. The results demonstrated that both pharmacological inhibition and iNOS knockout mitigated mitochondrial dysfunction, oxidative stress and Akt S-nitrosylation, leading to an ameliorated HFpEF phenotype in mice. In vitro, iNOS directly induced Akt S-nitrosylation at cysteine 224 residues , leading to oxidative stress, while inhibiting insulin-mediated glucose uptake in myocytes. Altogether, the present findings suggested an important role for iNOS in the pathophysiological development of HFpEF, indicating that iNOS inhibition may represent a potential therapeutic strategy for HFpEF.